2016
DOI: 10.1016/j.jjcc.2015.06.005
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between neutrophil to lymphocyte ratio, endothelial function, and severity in patients with obstructive sleep apnea

Abstract: NLR and endothelial dysfunction significantly correlates with the severity of OSA and FMD and other biochemical parameters improved and NLR decreased significantly after CPAP treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 46 publications
3
18
0
Order By: Relevance
“…In another study, male sex and age were also independent risk factors for severe SA in the elderly group 27. Moreover, a strong correlation has been reported between SA severity and biomarkers of systemic inflammation and oxidative stress 28,29. Therefore, it is reasonable to conclude that men and elderly patients have an increased risk of PD, assuming inflammation and oxidative stress play key roles in PD pathophysiology.…”
Section: Discussionmentioning
confidence: 95%
“…In another study, male sex and age were also independent risk factors for severe SA in the elderly group 27. Moreover, a strong correlation has been reported between SA severity and biomarkers of systemic inflammation and oxidative stress 28,29. Therefore, it is reasonable to conclude that men and elderly patients have an increased risk of PD, assuming inflammation and oxidative stress play key roles in PD pathophysiology.…”
Section: Discussionmentioning
confidence: 95%
“…Pathomechanisms between CVD and chronic kidney disease (CKD) are complicated, multifactorial, and yet not completely understood. Various processes, such as vascular calcification [ 1 ], endothelial dysfunction [ 27 ], and chronic inflammation, among others, significantly contribute to development of these diseases [ 28 ]. There is a variety of inflammatory markers, such as CRP [ 29 ]; however, they are expensive and imprecise.…”
Section: Discussionmentioning
confidence: 99%
“…In studies analyzing factors associated with OSAS severity in recent years, the common and strongest parameter obtained is obesity. [7][8][9][10][11][12][13] Tufik et al [21] reported that obesity was one of the independent risk factors for patients with AHI ≥15, regardless of gender. [21] Based on these data, we grouped our patients as obese (BMI >30 kg/m 2 ) and non-obese (BMI ≤29.9 kg/m 2 ) patients.…”
Section: Discussionmentioning
confidence: 99%
“…[2] The disease is associated with functional disorders such as excessive daytime sleepiness, daytime headaches, disrupted concentration, traffic and work accidents, in addition to somatic disorders including systemic and pulmonary hypertension, ischemic heart disease, and cerebrovascular disease. [3] Many authors have proposed a correlation of the disease or disease severity with a variety of inflammatory mediators, [4][5][6][7] biochemical markers, [8][9][10] and hormonal parameters. [11][12][13] Some studies have emphasized a correlation of the disease with respiratory tract anatomy and loss of genioglossus and pharyngeal muscle function causing pharyngeal collapse in individuals, although it is not possible to explain the problem with a single mechanism.…”
mentioning
confidence: 99%